The Oral Patrimony of a community in the construction of creative and Cultural Industries: A strategy for Cultural sustainability and Economic growth (2021)
The elements of the Cultural Herita!e have brou!ht new discussions and challen!es because despite the reco!nition of their value they have been idolized and consequently confined in museum cases, disconnectin! them from reality. This research has been developed from a Desi !n framework and explores how the narrative character of the Oral Patrimony is able to connect these resources with their contemporary context and bearers; thus cultural !oods become Storytellers (as any product), able to reveal their potential as resources of sustainable development at di#erent levels (cultural, economic, environmental, political, etc). Throu!hout some Desi!n strate!ies (Emotional Desi!n and Co-Desi!n) people – cultural bearers can become active users and consumers of their territory and cultural property and have a meanin!ful approach (supported by Storytellin!) that helps them to understand the potential of their Cultural Herita!e in the construction of Creative Industries and therefore of a Creative Economy.